A cyclic azapeptide ligand of the scavenger receptor CD36/SR-B2 reduces the atherosclerotic lesion progression and enhances plaque stability in apolipoprotein E-deficient mice - Gauvin, Jade; Frégeau, Geneviève; Elimam, Hanan; Ménard, Liliane; Huynh, David; Lê, Catherine; Ahsanullah, Ahsanullah; Lubell, William D.; Ong, Huy; Marleau, Sylvie (Frontiers in Pharmacology, 2023)
Atherosclerosis is a chronic inflammatory disease of the arterial walls that develops at predisposed sites. A major risk factor for adverse cardiovascular pathology, atherosclerosis can progress to myocardial infarction and stroke, due to rupture of unstable atherosclerotic lesions. Macrophage uptake of modified lipoproteins and metabolic dysfunction contributes significantly to the initiation and development of atherosclerotic lesions. The cluster of differentiation-36 receptor [CD36 (SR-B2)] plays a key role in atherosclerotic lesion progression and also acts as an efferocytic molecule in the resolution of advanced plaque. In previous studies, linear azapeptide CD36 ligands were shown to exhibit anti-atherosclerotic properties. In the present study, a novel potent and selective macrocyclic azapeptide CD36 ligand, MPE-298, has proven effective in protecting against atherosclerosis progression. Features of greater plaque stability were shown after 8 weeks of daily injections with the cyclic azapeptide in apolipoprotein E-deficient mice fed a high fat high cholesterol diet.